The largest players rule the media playground. - Cherry, S.M (IEEE spectrum)
The top media companies increasingly do a lot more than create content. The 12 companies outlined in this article deliver content via cable systems and the Internet. They also have investments in makers of personal video recorders (PVRs) and set-top boxes and suppliers of video on demand. Consider the former Moxi Digital, builder of a personal entertainment hub that can play DVDs and CDs and can function as a PVR and a set-top box. Moxi's investors, before Vulcan purchased it, included AOL Time Warner, Vulcan, and Scientific-Atlanta. Vulcan also owns Digeo, another hub maker, with which Moxi was merged. Eight of the companies listed-AOL Time Warner, Comcast, Disney, GE, Liberty Media, Sony, Viacom, and Vulcan-were investors in ReplayTV before it was bought by SonicBlue. TiVo, an up-and-coming PVR maker, has attracted hefty investments from almost all major media companies. The most-connected company is AOL Time Warner. Under its umbrella one of its several movie or TV studios can create a film that gets shown on its HBO channel via the Time Warner cable system. Only US business interests are shown here. Many have overseas media holdings, notably France's Vivendi Universal, Japan's Sony, and News Corp. in Australia